Phenotypic stability of genotypes Lolium sp. in the high tropic of Nariño, Colombia - Cadena-Guerrero, Máryory Maricela (2019)
Introduction. The species of the Lolium genus represent an important component in the bovine feeding in several regions of Colombia, however, in the high tropic of Nariño, one of the main dairy basins of the country, there is little knowledge about the performance of the cultivars managed by the producers; there are no stability studies that allow us to know which of the cultivars offered in the market behave better in a specific location, which affects the farmers’ economy. Objective. The objective of this research was to determine the phenotypic stability of the yield of green forage (RFV) and dry matter (RMS) in ryegrass, in the dairy basin of the high tropic of Nariño. Materials and methods. Between 2016 and 2017, ten ryegrass genotypes were evaluated in Pasto, Cumbal, and Sapuyes. The experiments were established under a randomized complete block design with four repetitions. For the analysis of adaptability and stability of RFV and RMS, the model proposed by Eberhart and Russell, and the analysis of principal additives effects and multiplicative interactions (AMMI) were used. Results. The Tetralite II, Bóxer, Bestfor Plus, and Aubade genotypes had the highest green forage yields (7.52-8.34 t.ha.cut-1) and dry matter (1.29-1.37 t.ha.cut-1) in the three environments studied. With the Eberhart and Russell model, for RFV, these genotypes were classified as the best response in favorable and predictable environments, and by RMS they were also predictable, but Aubade and Bestfor Plus were classified with good response in all environments, and Bóxer and Tetralite II, with better response only in favorable environments. Conclusion. The AMMI model allowed to identify the Pasto municipality as the most favorable environment, and the Bóxer and Tetralite II genotypes as those with the best performing in this environment.